Embrace the SEC - Usha R. Rodrigues (Washington University Journal of Law & Policy, 2020)
Securities law traditionally only permits corporations that have registered with the Securities and Exchange Commission (SEC)and completed an initial public offering (IPO) to sell equity to the general public—often a long, expensive process. The initial coin offering (ICO) emerged in 2013 as a fundraising tool private blockchain-based companies have used over the past several years to raise billions of dollars, seeking to circumvent registration with the SEC and the public offering process altogether. But their early success brought the attention of the SEC, and in 2017 the SEC clearly asserted the right to regulate ICOs. Since then U.S. ICO promoters have struggled to avoid the SEC’s assertion of jurisdiction, contorting their offerings in an effort to avoid regulation. They have largely failed. This piece argues that government regulation is a feature, not a bug for ICOs. If ICO entrepreneurs acknowledge SEC jurisdiction—and if the SEC, for its part, implements creative mechanisms to protect investors – blockchain businesses can raise capital from the general public while continuing to serve the underlying goals of U.S. securities law.
Keywords: fintech; financial; financial services; financial technology; finance; finance law; law; technology law; securities regulation; sec reg; SEC; bitcoin; ICO